32 False alarms: code stemi activation's by stemi mimics – a primary PCI centre experience. (October 2018) - Hughes, D; Madders, G; Gorecka, M; Crowley, J
Abstract : Introduction: ST Elevation has a high sensitivity but a relatively low sensitivity of diagnosing an acute myocardial infarction (MI). STEMI (ST Elevation Myocardial Infarction) mimics are cases that have ST segment elevation on a 12 lead ECG but where occlusive coronary artery disease is out ruled as the cause of presentation. International literature suggests that these cases represent approximately 7%–14% of all code STEMI activation's. These represent an important cohort as they cause a significant workload for a primary PCI centre and expose patients to the risk of an invasive procedure. Methods: We conducted a retrospective review of all consecutive CODE STEMI activation's in our institution from 1st January 2016 to 31st December 2017. A STEMI mimic is defined as an activation of the STEMI pathway with ST segment elevation on a 12 lead ECG without angiographic evidence of occlusive coronary artery disease, or an acute MI being ruled out on clinical or biochemical grounds. We collected demographics on the patients and divided the cohorts by the location of the activation. Patients who were assessed by a physician prior to activation of the pathway were designated hospital activation (HA) and patients assessed by ambulance personal were designated field activation (FA). Results: During the 2 year period of our study we had 586 activation's of the code STEMI pathway. 451 (77%) patients had a final diagnosis of a STEMI, of the remaining 135 there were 21 acute coronary syndrome patients, 2 aborted STEMI's and 29 NSTEMI's. Therefore there were 83 STEMI mimics cases representing 10.5% of all activation's. Table 1 details the demographics and results of the study. The vast majority, 89%, of the mimic group underwent an angiogram. The subsets were very similar in terms of percentage of men, 74% for the STEMI group versus 75% for the mimic group and the number of field activations, 46% in the STEMI group versus 40% for the mimic group. The only significant difference between the cohorts was that the mimic group were younger with a mean age of 58 versus a mean age of 66 in the STEMI group. Figure 1 details the final diagnosis for each mimic case. The most common diagnosis was of non-cardiac pain (53%), followed by pericarditis (24%), arrhythmia (10%), myocarditis (7%) and takotsubo cardiomyopathy (6%). Conclusions: False activation of the code STEMI pathway is a significant concern due to the exposure of unnecessary risk of the procedure to the patient and also the resource implications. The only significant difference between the cohorts was that the STEMI mimics patients were younger. There was no difference statistical between field activation and hospital activation, which may reflect that in our institution all ECG's are reviewed by a cardiology registrar prior to activation of the code STEMI pathway. During our study our false activation's accounted for 10% of all cases, which correlates well with international standards, however it highlights an area for further educational work with ambulance paramedics, general practitioners and emergency department staff.